2010
DOI: 10.1007/s00380-009-1155-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of coronary atherosclerosis in patients with coronary artery disease

Abstract: The distribution of coronary atherosclerosis has not been fully clarified. We measured coronary artery calcium score (CACS) in 624 consecutive patients for the right coronary artery (RCA), left main trunk (LMT), left anterior descending coronary artery (LAD), and left circumflex coronary artery (LCx), then calculated total CACS. Coronary artery calcium score was measured using the Agatston method. We divided these patients into four groups: CACS 1-100 (Group A, n = 267), CACS 101-400 (Group B, n = 160), CACS 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Capodanno et al [25] investigated the epidemiology and the clinical impact of different anatomical phenotypes of the LM coronary artery, and Iwasaki et al [26] investigated the distribution of coronary atherosclerosis in patients with CAD. Their findings suggested that LM phenotypes are more likely to present with atherosclerotic disease and significant stenosis and are particularly heritable [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Capodanno et al [25] investigated the epidemiology and the clinical impact of different anatomical phenotypes of the LM coronary artery, and Iwasaki et al [26] investigated the distribution of coronary atherosclerosis in patients with CAD. Their findings suggested that LM phenotypes are more likely to present with atherosclerotic disease and significant stenosis and are particularly heritable [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease is a leading cause of death in developing and developed countries [2,17]. No uniform guidelines exist for the postoperative prevention of thrombotic complications after CABG [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Fischer et al [16] reported that 9 of 12 monozygotic twin pairs displayed concordance for LM lesions, whereas only 3 of 12 were concordant for MP lesions [28,29], suggesting genetically involvement. Capodanno et al [30] investigated the epidemiology and the clinical impact of different anatomical phenotypes of the LM coronary artery and Iwasaki et al [31] investigated the distribution of coronary atherosclerosis in patients with CAD. They findings suggested that LM phenotypes are more likely to present with atherosclerotic disease and significant stenosis [30] and are particularly heritable [31].…”
Section: Discussionmentioning
confidence: 99%